Determinants of Malaysia export on natural rubber: an empirical evidence / Najihah Shamsuddin - Shamsuddin, Najihah (Faculty of Business and Management, 2006)
This study is concern with the determinants of export on natural rubber in Malaysia and the empirical evidence. The objective is to study the trend of natural rubber, to estimate the determinant on supply of natural rubber and to analyze the supply elasticity on supply of natural rubber in Malaysia from first quarter 1997 until fourth quarter 2003. Independent variable that has been identifying to complete the study, which is price of natural rubber, price of synthetic rubber, price of crude oil, exchange rate, tyre production and gross domestic product (GOP) per capita. Because of the fluctuation happen during the period of time, researcher interested to know the factors influencing the fluctuation in quantity supply of natural rubber in Malaysia. To meet the objective, researcher has used three method of study. For trend analysis, researcher want to figure out the fluctuation happen on independent variable during the period of time. In addition, for supply estimation, researcher used econometric model to analyze the data while supply elasticity calculated using ordinal least square (OLS).The study found that among the independent variable, there are only three variables that significant with the objective which is price of natural rubber, price of crude oil and gross domestic product (GOP) per capita. From the estimation result, it shows that synthetic rubber becomes the complementary goods for natural rubber. In addition, elasticity output shows that price of natural rubber is inelastic during the period of time.